Cardiac arrest in non-ST segment elevation myocardial infarction: what to expect. (2nd May 2022) - Carvalho, P; Goncalves, F; Monteiro, J; Bernardo, M; Carvalho, C; Fontes, P; Moreira, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Ischemic heart disease is the leading cause of cardiac arrest (CA). While in ST segment elevation myocardial infarction its approach is well defined, in non-ST segment elevation myocardial infarction (NSTEMI) it is still a matter of debate. This study aimed to characterize patients with NSTEMI and out-of-hospital CA and to evaluate its prognosis. Methods: This was a national multicenter retrospective study of patients hospitalized for NSTEMI undergoing coronary angiography (ANG) between October 2010 and September 2019. Results: Out of a total of 9544 patients, 96 were admitted after CA. The baseline characteristics of both groups were similar, with the exception of more past history of heart failure (10, 5% vs 5, 6%, p=0, 038) and peripheral artery disease (11, 5% vs 5, 9%, p=0, 023) in patients with CA. In the peri-arrest period, 64, 6% of the patients reported chest pain. Patients with CA had worse left ventricular ejection fraction (49±13% vs 53±12%, p=0, 006), ended up reaching higher Killip classes more often and needing more inotropic and mechanical support. The median time from admission to ANG was similar in both groups (0 (0;3) vs 1 (0;2) days, p=0, 796). CA patients had more multivessel coronary disease (66% vs 55, 5%, p=0, 043) and left main artery involvement (25, 3% vs 11, 2%, p<0, 001). The proportion of revascularization procedures was similar. During hospitalization, patients with CA were less treated with beta-blockers (77, 9% vs 85, 2%, p=0, 046) and ACE inhibitors (77, 7% vs 86, 1%, p=0, 018), a difference that disappeared at discharge. However, statin prescription at discharge was lower in CA patients (88, 3% vs 94, 4%, p=0, 040). In a multivariate analysis for events occurred during hospitalization, CA was associated with a significant increase in myocardial reinfarction (adjusted OR 5, 42 (95% CI 2, 10-1, 98)), stroke (adjusted OR 5, 38 (95% CI 1, 24-2, 32)) and death (adjusted OR 13, 86 (95% CI 5, 98-32, 17)). After excluding patients with indication for an immediate invasive strategy, we verified that mortality was higher in CA patients who underwent ANG in the first 24 hours. CA was not associated with a significant increase in the 1-year mortality rate (adjusted HR 0, 67 (95% CI 0, 10-4, 90)). Conclusions: In this study, NSTEMI patients surviving CA had more severe coronary events. CA was independently associated with a significant increase in in-hospital major adverse events. However, during the 1-year follow-up there was no significant increase in mortality.